2007
DOI: 10.1111/j.1365-2929.2006.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' learning of anatomy: memorisation, understanding and visualisation

Abstract: Approaches to learning correlate positively with the quality of learning. Successful learning of anatomy requires a balance between memorisation with understanding and visualisation. Interrelationships between these three strategies for learning anatomy in medicine and other disciplines require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
229
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(247 citation statements)
references
References 27 publications
10
229
1
7
Order By: Relevance
“…None of the students in this study indicated that they had memorised names and structures as evident in a study by Pandey & Zimitat (2007). These authors suggested that students often learn anatomy by adopting more than two approaches, such as using a combination of visual stimulation, understanding and/or memorisation.…”
Section: Discussionmentioning
confidence: 89%
“…None of the students in this study indicated that they had memorised names and structures as evident in a study by Pandey & Zimitat (2007). These authors suggested that students often learn anatomy by adopting more than two approaches, such as using a combination of visual stimulation, understanding and/or memorisation.…”
Section: Discussionmentioning
confidence: 89%
“…Pandey and Zimitat showed a significant positive correlation between DA and achieving a higher quality learning of Anatomy. This was not observed for SA alone (Pandey and Zimitat, 2007). Larsen et al (2008) reviewed the evidence for testenhanced learning in cognitive psychology.…”
Section: Introductionmentioning
confidence: 98%
“…Students learning Anatomy are required to spend considerable time learning a large number of body structures together and the relationships with other structures of the body. Anatomy may be one discipline where distinctions between deep and surface learning strategies are blurred (Pandey and Zimitat, 2007). Students who successfully learn Anatomy employ both superficial (SA) and deep approaches (DA) to learning.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies that additionally involved Virtual Reality (VR) and direct manipulation interfaces have demonstrated a positive impact in shortening the learning curve in medical training [3,4,5,6]. A fusion of CT and VR has also been used in clinical applications where interventional radiologists utilised this combinatory approach for performing percutaneous controlled radiofrequency trigeminal rhizotomy (RFTR) assisted by a VR imaging technique for idiopathic Trigeminal Neuralgia [7].…”
Section: Introductionmentioning
confidence: 99%